Evaluation of arrhythmias associated with sudden cardiac death in paediatric patients. Issue 2 (February 2017) - Walsh, Mark; Stuart, Graham; Martin, Rob
Abstract: In the last decades we have seen an increased focus on the prevention of sudden cardiac death (SCD). There is much controversy regarding the most appropriate screening programs where we attempt to balance potentially preventable cases of SCD with the cost of screening programs in addition to the anguish caused by false positive results. Recent events have also demonstrated to us the danger of strenuous exercise in people who have a genetic susceptibility to SCD, whatever the mechanism may be. Also, the barrage of genetic testing now available to us provided us with a new clinical problem, those who are genotype positive but yet do not show any manifestations of the disease. Syncope is very common in the paediatric age group and its evaluation is the cause of much anxiety. As physicians, we would rather not over investigate what is probably a benign condition; however, a missed diagnosis has potentially catastrophic consequences. In this review we will outline the various cardiac pathologies involved, how they are diagnosed, what the potential implications are for the patient and the best available therapeutic options.